(untitled) (Ciudades, 2025)
The study analyzes the relationship between post-relocation residential satisfaction and sociodemographic characteristics in segregated social housing in Manizales, Colombia, and Concepción, Chile. Under an intersubjective paradigm, with an interdisciplinary and quantitative approach, surveys and nonparametric tests were used to compare satisfaction between sociodemographic groups within the housing typologies of each case. The findings reveal that women have lower satisfaction, family size has a negative relationship, and age, income, length of residence, and satisfaction in the previous home are positively correlated with satisfaction. These links depend on the dimension of the residential environment evaluated, the housing typology, and the context.